Total body irradiation causes a chronic decrease in antioxidant levels - Sun, Lue (Sci Rep, 2021)
Ionizing radiation exposure may not only cause acute radiation syndrome, but also an increased risk of late effects. It has been hypothesized that induction of chronic oxidative stress mediates the late effects of ionizing radiation. However, only a few reports have analyzed changes in long-term antioxidant capacity after irradiation in vivo. Our previous study demonstrated changes in whole-blood antioxidant capacity and red blood cell (RBC) glutathione levels within 50 days after total body irradiation (TBI). In this study, seven-week-old, male, C57BL/6J mice exposed to total body irradiation by X-ray and changes in whole-blood antioxidant capacity and RBC glutathione levels at ≥ 100 days after TBI were investigated. Whole-blood antioxidant capacity was chronically decreased in the 5-Gy group. The RBC reduced glutathione (GSH) level and the GSH/oxidative glutathione (GSSG) ratio were chronically decreased after ≥ 1 Gy of TBI. Interestingly, the complete blood counts (CBC) changed less with 1-Gy exposure, suggesting that GSH and the GSH/GSSG ratio were more sensitive radiation exposure markers than whole-blood antioxidant capacity and CBC counts. It has been reported that GSH depletion is one of the triggers leading to cataracts, hypertension, and atherosclerosis, and these diseases are also known as radiation-induced late effects. The present findings further suggest that chronic antioxidant reduction may contribute to the pathogenesis of late radiation effects.